The Effect of Smart Fun Alphabet Media on the Ability to Recognize Letters for Early Childhood - Ristianti, Villi Widia; Sari, Wulan (International Journal Education and Computer Studies (IJECS), 2024)
Children are distinctive individuals with unique characteristics encompassing cognitive, social, emotional, linguistic, physical, and artistic aspects that are undergoing a rapid developmental process. This phase signifies a crucial period laying the foundation for future life trajectories. Consequently, the age bracket of zero to six years is deemed as the optimum developmental stage. The primary objective of this investigation is to ascertain the impact of intelligent and enjoyable alphabet media on children's letter recognition abilities, particularly focusing on early childhood in Ar-rohman PAUD Bantunan Village, Pajar Bulan District, Lahat Regency. This study adopts a field research design, employing a quantitative approach, with a total sample size of 24 individuals and utilizing observation and documentation as data collection methods. The data analysis entails statistical analysis through the T-test. The findings reveal that the statistical analysis of paired t-tests yielded a t count of 92.916, surpassing the critical t table value of 2.096 (92.916 > 2.069) with a significance level of 0.000 < 0.005. Consequently, the null hypothesis (H0) is rejected in favor of the alternative hypothesis (Ha), with a correlation coefficient (R) value of 0.895. This indicates a highly robust relationship between the research variables. The R Square value, or coefficient of determination (KD), stands at 0.800, suggesting that the independent variable X exerts an influencing effect of 80% on variable Y. The remaining 20% signifies the contribution of unaccounted variables within the study.